Diseño de una red de sensores inalámbricos (WSN) de bajo consumo energético para el monitoreo estructural de puentes - Pineda Chamba, Jhanes Alexander (2024)
The present thesis focuses on the design of a wireless sensor network based on LoRa technology for structural conditions of bridges monitoring. The sensor network was designed to measure and monitor key physical variables that include temperature, humidity, wind speed and vibrations. To achieve this, a variety of sensors were used, including the DHT22 for temperature and ambient humidity measurement, the ADXL345 for vibration detection, the SW-420 for seismic motion detection, and an anemometer for wind speed measurement. The data collected by the sensors were transmitted through the LoRa network and sent to The Things Network (TTN) platform for processing and storage in the cloud. Subsequently, the integration of this data with the Ubidots platform was carried out, which allowed its visualization and analysis in real-time. The main purpose of this thesis was to develop an efficient and reliable solution for the continuous monitoring of the structural condition of bridges using IoT and LoRa technology. Keywords: LoRa, Sensors, The things networks, Ubidots, IoT, smart cities.